THE COMPARISON BETWEEN AUDITORY LEARNERS AND VISUAL LEARNERS’ ACHIEVEMENT IN WRITING SKILLS OF THE STUDENTS IN THE ENGLISH EDUCATION DEPARTMENT UIN ALAUDDIN MAKASSAR - Rahim, Muthi’ah (English Language Teaching for EFL Learners Journal, 2019)
This quantitative research is aimed to find out (1) the writing quality of both visual and auditory learners; (2) whether or not the writing quality of auditory learners is significantly different from that of visual learners; and (3) which type of learners has better writing quality. This research applied causal-comparative design in analyzing and comparing the writing skills between the visual and auditory learners. The research participants were the sixth semester students of English Education Department UIN Alauddin Makassar in the academic year of 2017-2018. The data were collected using two kinds of instruments, namely Perceptual Learning Style Inventory and writing test. The results showed that both the visual and auditory learners are in normal criteria of writing quality, and also, there is not any significant difference of writing quality between auditory learners and visual learners. Nevertheless, auditory learners had a tendency to outweigh the visual learners in terms of the total score regardless the insignificancy of the difference. On the other hand, the significant difference of the mean score found from the t-test result underscores the ideas that the learning styles and other contributing factors to writing production to satisfy students’ learning are consistent with the theories used in this study. It proves that every individual’s learning preferences differ significantly, and the stronger the preference, the more important it is to provide compatible learning and teaching strategies which involve students’ strategies, knowledge and purposes.